Desempenho bioeconômico de ovinos alimentados com rações contendo farelo de mamona destoxificado - Vieira, Marieta Maria Martins (2009)
To evaluate the effect of substitution of soybean meal by detoxified castor meal on consumption and performance of sheep this research was carried out. Twenty crossbred lambs, male, whole, weighting 19.3 ± 1.35 kg, averaging 7 months of age were randomly assigned to four treatments of 0, 50, 75 and 100% of substitution, on dry matter basis, were used the roughage used was elephant grass (Pennisetum purpureum Schum.) hay. The diets were balanced to be isonitrogenous and isocaloric, delivered in two daily meals, collecting the following day the leftovers, which were weighed, keeping them around 15%. The experiment lasted for 70 days, when animals were slaughtered. The experimental trials were conducted in a completely randomized design with four treatments and five repetitions. In the assessment of ingestive behavior, the parameters of feeding time, ruminating, other activities, leisure, consumption of salt and water intake were affected by treatments and periods of the day. The urination and defecation were affected only by time of day, in jaw movements per ruminal bolus there was inferior to 100% substitution. In the assessment of consumption and performance, there was a significant difference to the feed conversion, determining that the 50% level of substitution improved better performance of animals. However, there was no significant difference for average daily gain and number of days to reach 12 kg. The regression analysis showed a quadratic effect for the feed conversion, with a biological optimum level to 59% substitution of soybean meal by detoxified castor meal. There were no significant differences for the intake of dry matter, neutral detergent insoluble fiber, acid detergent insoluble fiber, hemicellulose and mineral matter (in g/animal x day, % BW, and g/UMS). There was less consumption of ether extract for the 75% level of substitution and crude protein levels in 50 and 75% for replacement. Related to carcass evaluation and non carcass components, no significantly differences were observed among the levels of substitution for the variables body weight, weight of slaughter, losses due to fasting, hot carcass weight, cold carcass weight, cooling losses, length of carcass, hip of perimeter, hip width and degree of resignation. The regression analysis showed a quadratic effect for real and biological yields, with a great organic level of 100% substitution. In non carcass components, no significantly differences were registered for viscera, full gastrointestinal tract, empty gastrointestinal tract, genitals, head and legs. For the variable skin, the regression analysis showed a quadratic effect, presenting a point of maximum at 44% for replacement. Castor bean meal can substitute 100% of soybean meal. The result of the economic analysis of food offered in the experiment, showed that none of the treatments were profitably. Moreover, considering the gross (US$/kg BW), net (US$/kg BW) and profit (US$/kg BW) margins obtained, it appeared that only the level of 0% substitution showed positive values for such indices (US$ 0.31/kg BW, US$ 0.29/kg BW and US$ 0.26/kg BW, respectively), when the selling price of live weight was of US$ 2.26. The replacement of up to 100% of soybean meal by detoxified castor meal do not alter significantly the ingestive behavior of lambs finished in feedlot. Detoxified castor bean meal shows potential for use as feed for sheep in termination, promoting lower consumption of crude protein with no change in average daily gain at 100% and good feed conversion, at 59% for replacement. The characteristics of the carcass and non carcass components were not affected by use in up to 100% of substitution, and the variable skin presented a biological level optimum when the soybean meal was replaced in 44% by detoxified castor meal. The use of autoclave-detoxified castor meal in rations for termination of lambs is not presented as a good alternative to guarantee profits to the producer, as this activity would only be viable when the sale price of the lamb is higher than US$ 4.03/kg BW